2017
DOI: 10.1097/rct.0000000000000537
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gaussian Diffusion Imaging Shows Brain Myelin and Axonal Changes in Obstructive Sleep Apnea

Abstract: Objective Obstructive sleep apnea (OSA) is accompanied by brain changes in areas that regulate autonomic, cognitive, and mood functions, which were initially examined by Gaussian-based diffusion tensor imaging measures, but can be better assessed with non-Gaussian measures. We aimed to evaluate axonal and myelin changes in OSA using axial (AK) and radial kurtosis (RK) measures. Materials and Methods We acquired DKI data from 22 OSA and 26 controls; AK and RK maps were calculated, normalized, smoothed, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…The present study differs from Tummala's study on OSA ( 37 ), which found increased kurtosis parameters in several intracranial regions. They suggested that the hypoxic and ischemic damage caused by OSA may cause swelling of neurons and axons, leading to acute axonal and myelin tissue damage.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study differs from Tummala's study on OSA ( 37 ), which found increased kurtosis parameters in several intracranial regions. They suggested that the hypoxic and ischemic damage caused by OSA may cause swelling of neurons and axons, leading to acute axonal and myelin tissue damage.…”
Section: Discussioncontrasting
confidence: 99%
“…The compromised WM fiber tracts observed in this study reside in autonomic or respiratory control regions (insular cortices, midline pons, cerebellar peduncles, and cerebellar vermis), as well as in neuropsychologic, motor, or cognitive regulatory areas (hippocampus, amygdala, internal and external capsules, ventral putamen, frontal, parietal, and temporal white matter regions), all of which are relevant to OSA [50]. For example, the corona radiata propagates from the frontal/parietal cortex to the brain stem via internal capsule, which involves a number of fiber tracts (e.g., ACR.R, ALIC.R, PLIC.R, ALIC.L).…”
Section: Discussionmentioning
confidence: 99%
“…Further improvement may also be achieved by including BMI as another covariate. Like several other recent imaging studies on OSA [5,50,52], the present study did not include BMI as a covariate because of the following reasons. First, although individuals with higher BMI tend to have a higher prevalence of OSA, WM change affected by BMI has not been fully established in the literature, despite recent reports on a limited number of tracts [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…In a related approach, diffusion imaging studies reveal widespread alterations in white matter integrity in sleep apnea patients relative to controls, particularly in regions implicated in sleep/wake control and cognitive functioning (bilateral prefrontal cortex, hippocampus, amygdala, insula, cerebellum, medulla, pons, basal forebrain, basal ganglia, right posterior parietal lobe, and right occipital cortex)[104]. Greater apnea-hypopnea index [105], via acute hypoxic injury [106, 107], worsens the negative effects of sleep apnea on white matter integrity.…”
Section: Neuroimaging Studies In Patients With Sleep Disordered Breatmentioning
confidence: 99%